2017
DOI: 10.20428/yjms.11.1.a7
|View full text |Cite
|
Sign up to set email alerts
|

Fighting fake medicines: Quality evaluation of seven brands of Albendazole tablets in Yemeni Market

Abstract: Objective: To assess certain quality control parameters for seven brands of albendazole tablets obtained from different retail pharmacies. Methods:The physicochemical properties and active ingredientsofseven randomly selectedbrands of albendazole tablets were assessed weight uniformity, hardness, friability, disintegration and dissolution Results: All seven albendazole brands met the British Pharmacopeia (BP) quality control standards of weight uniformity, friability and the active ingredient content. Five bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…In this study, assessment of the weight uniformity revealed that four batches did not meet the criteria. In contrast to the finding of this study, absence of variation was reported by Othman [16] in Yemen. The difference may be related to the manufacturing practices.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, assessment of the weight uniformity revealed that four batches did not meet the criteria. In contrast to the finding of this study, absence of variation was reported by Othman [16] in Yemen. The difference may be related to the manufacturing practices.…”
Section: Discussioncontrasting
confidence: 99%
“…A relatively high prevalence of poor quality of albendazole was also reported in a separate study by Suleman et al [21] in Ethiopia. In Yemen, Othman [16] assessed the quality of seven brands of albendazole and found that only two brands fulfil the British Pharmacopeia quality control standards. The presence of counterfeit anthelminthic drugs was also reported by Khan et al [8] in Cambodia.…”
Section: Discussionmentioning
confidence: 99%
“…To be effective a drug should have the required physicochemical qualities and should be sterile. The quality of a drug might be affected by the storage conditions, humidity, packaging materials, transportation, formulation, the nature of the active ingredient, and the presence of microorganisms (Othman, 2017;WHO, 2019). The pharmaceutical products should constitute not only an adequate amount of API but also must be packed with proper packaging materials in the desired container, which protects environmental conditions that may affect the quality of the products.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the friability test is a quality test requirement for assuring the tablet's resistance to abrasion during packaging, handling, and transportation 39 . If the tablet is friable, the amount of API present in the formulation will be under the required amount and cause a problem of content uniformity in product 28 . All this will decrease the bioavailability of the drug and customer trust in the product 40 .…”
Section: Friability Testmentioning
confidence: 99%
“…Then 13.5 ml of sample solution from each glass beaker was taken and transferred into individual 25 ml volumetric flasks using a volumetric pipette. As a result, it was subjected to suitable dilution (adding a diluent to a volume of 25 ml) to get the accepted sample concentration of 0.015 mg/ml (125%) 28 and analyzed by using UV-Visible spectroscopy at the wavelength of 272 nm at which maximum absorbance appear under the test 24 . The absorbance of the sample was measured.…”
Section: Dissolution Testmentioning
confidence: 99%